(untitled) (Моделювання, керування та інформаційні технології, 2019)
This article examines the use of Building automation system to give comfortable conditions for users to provide improving energy efficiency. We found out the impact of the Internet of Things concept on BAS development, and how the use of modern wireless technologies, edge and cloud computing is determining the way of the following progress. Also, their advantages and disadvantages were considered. A separate section focuses on the state of BAS in Ukraine and the key factors that influence it